2020
DOI: 10.21203/rs.3.rs-67761/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pregnant Women’s Health-related Behavior Changes and Psychological Status After the Peak of COVID-19 Outbreak in China: A Cross-sectional Study

Abstract: Background: Little is known about the relationship between health-related behavior and psychological status of pregnant women during the COVID-19 outbreak. We aimed to describe the health-related behavior changes and psychological status of Chinese pregnant women, and to explore the relationship between pregnant women’s characteristics, health-related behavior and different psychological status following the peak of COVID-19 outbreak.Methods: We conducted an online survey through social media (WeChat) from Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In China, previous studies reported that pregnant women went out less, and about two-fifths of pregnant women did not undergo prenatal examination or did not have antenatal visits on time after the peak of the outbreak of COVID-19. 13 Similarly, Yue et al 14 found that pregnant women take protective measures such as wearing masks, washing hands frequently, cleaning, and disinfecting their homes to avoid virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…In China, previous studies reported that pregnant women went out less, and about two-fifths of pregnant women did not undergo prenatal examination or did not have antenatal visits on time after the peak of the outbreak of COVID-19. 13 Similarly, Yue et al 14 found that pregnant women take protective measures such as wearing masks, washing hands frequently, cleaning, and disinfecting their homes to avoid virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted during the Coronavirus pandemic found that pregnant women often perform PHB due to COVID-19 [27,28]. For example, in a study conducted in Colorado among pregnant women, it was found that all of the women reported changes in their health behaviors during the Coronavirus pandemic, which included increasing the frequency of hand washing, frequent use of antiseptic gel, reducing meetings with friends (social distancing), avoiding people who had symptoms of Coronavirus, using masks, and avoiding touching the face, nose, and mouth [29].…”
Section: Health Behaviors Among Pregnant Womenmentioning
confidence: 99%